DRAMATURGI PROFESI BARISTA DI NORMA COFFEE SHOP DAN CIPADAS COFFEE SHOP PEKANBARU - Jihan Noprinah; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The rapid interest of young people to pursue the barista’s in Indonesia is influenced by the values and existence of social media. The phenomenon of barista dramaturgy on social media shows that there is a disparity in baristas who seek this profession to fulfill their daily needs. This study uses a descriptive qualitative research approach using the purposive sampling technique. Data was collected through in-depth interviews, observation, and documentation. The results show that baristas build personal branding on social media for self-existence and increase coffee shop marketing, but in the world of work personal branding is done to improve professionalism as a barista. Baristas who make this profession their main source of income cannot meet their daily needs because the income is not commensurate with the barista's dependents and lifestyle. The front stage of the barista can be seen from the way the barista builds personal branding in the media and professionalism at work. However, for Back Stage life, it can be seen from the discussion of lifestyle and income as a barista. Keywords: Dramaturgy (Front Stage, Back Stage), Barista, Social Media.